Gender Dimensions of Child Labor and Street Children in Brazil - Gustafsson-Wright, Emily; Pyne, Hnin Hnin (World Bank, Washington, DC, 2014)
The authors review child labor and the situation of street children in Brazil from a gender perspective. Relying primarily on Brazil's national household survey for 1996, the authors examine various dimensions of child labor by gender, including participation, intensity, and type of activities; the relationship between child labor, education, and future earnings; and the risks of child labor to health and well-being. They also summarize approaches to prevent and eliminate child labor and street children in Brazil. The authors find that more boys than girls work in Brazil especially in rural areas where boys are concentrated in the agricultural sector, that many children both work and attend school, and that girls attain higher levels of education than boys on average, even when considering number of hours worked. The exception is the 11-14 category. They also find that an individual's earnings are correlated with age of entry into the labor market. The earlier a child begins to work, the lower his or her earnings. And girls are more adversely affected by early labor force entry than boys, with the gender differential increasing the earlier a child begins to work. Taking poverty as the primary contributor to child labor, government programs to combat child labor are well designed in that they compensate families for a child's foregone earnings and address family factors that lead to poverty. However, programs could be improved by explicitly considering the gender dimensions of child labor. The authors point to the need for analysis of the impact of child labor on health, and specifically to the gender and sex-differentiated impacts. They suggest the need to address gender in intervention strategies for street children, as well as research on child labor in domestic service where girls are overrepresented.